Oral Hygiene Maintenance Behavior and Community Periodontal Index in Systemic Lupus Erythematosus Patients: A Correlational Study - Betty Saptiwi; Widia Susanti; Alfiyah Pujiyati; Risya Cilmiaty; Adi Prayitno; Ignatia Widiastuti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder that commonly presents with oral manifestations, including xerostomia, mucosal ulcerations, dental caries, and periodontitis. Periodontitis, characterized by progressive destruction of tooth-supporting tissues, is frequently aggravated by inadequate oral hygiene practices. This study aimed to investigate the correlation between oral hygiene maintenance and periodontal health in patients diagnosed with SLE. Methods: This study employed a cross-sectional correlation design. It involved 100 participants, comprising 50 SLE patients and 50 healthy controls subjects, recruited through purposive sampling. Periodontal health was assessed using the Community Periodontal Index (CPI). Oral hygiene maintenance behavior was assessed using a self-administered structured questionnaire, adapted and modified from the Hiroshima University–Dental Behavioral Inventory (HU-DBI). Differences in community periodontal index between the SLE and control groups were analyzed using a Mann-Whitney test. The relationship between oral hygiene behaviors and CPI scores was examined using Spearman’s rank correlation test. Results: The results revealed that SLE patients exhibited poorer oral hygiene knowledge, attitudes, and practices compared to healthy controls subjects, along with significantly worse periodontal health (p < 0.05). Furthermore, Spearman’s rank correlation test showed significant negative correlations between oral hygiene maintenance behaviors and CPI scores in the SLE group (r = - 0.156, p < 0.05; r = - 0.148, p < 0.05; r = - 0.148, p < 0.05, respectively) indicating that patients who practiced better oral hygiene tended to have lower CPI scores and, consequently, healthier periodontal status. Conclusion: Improved oral hygiene practices are significantly correlated with enhanced periodontal health in patients with SLE. These findings underscore the importance of emphasizing effective oral hygiene measures as part of comprehensive periodontal management strategies for SLE patients.